Proposal stage coalition-building in the European Parliament - Finke, Daniel (European Union politics, 2012)
Almost all existing studies of conflict and coalitions inside the European Parliament (EP) rely on the statistical analysis of voting behaviour. Yet who proposes the alternatives put to vote? Which political groups jointly co-author legislative amendments? Which strategic considerations (if any) determine legislative coalition-building inside the EP? To answer these questions, this article analyses information on the proposer identity for all legislative amendments drafted in the sixth legislative period. My findings suggest that, when building coalitions, political groups consider the degree of inter-institutional conflict. However, despite the highly proportional rules of procedure, the rapporteur emerges as the most powerful player in proposal stage coalition-building. Other groups may successfully challenge the rapporteur only if they aim at pulling the draft report closer to the floor median. Those who are interested in pulling the outcome away from the median have little choice but to include the rapporteur as a member of their coalition. In this case, rapporteurs must strike a fine balance between convincing their fellow Members of the European Parliament of the strategic exigency of deviating from the median and maintaining their credibility when bargaining with the members of the Council. If rapporteurs are too close to the Council, they forfeit their trustworthiness among their potential coalition partners.